Pentingnya Pelestarian Budaya pada Rumah Gadang Mande Rubiah di Nagari Lunang - Elsa Elsa; Solfema Solfema; Lili Dasa Putri (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Cultural heritage in West Sumatra, one of which is located in the Pesisir Selatan Regency, Nagari Lunang which has high socio-cultural and historical value, namely Rumah Gadang Mande Rubiah. Not only does it function as a traditional building but Rumah Gadang is also the center of deliberations between grandfather, penghulu, ninik mamak, alim ulama and cadiak pandai who are there, and also various traditions and cultures that exist in Rumah Gadang, such as batagak panghulu, manjalang Rumah Gadang mande rubiah, bathing balimau, and also marriage events. In addition, Rumah Gadang also holds a large collection of heirloom krises, tambo, coins / papers, garuda bird eggs, typical Minangkabau carvings. Therefore it is important for the community and mande rubiah to preserve the Rumah Gadang and maintain cultural identity and also as a source of learning for young generations. Rumah Gadang has important potential, so it must be preserved and the characteristics of the Gadang House, in order to maintain cultural identity and as a source for the next generation. This study reviews what traditions are carried out, Rumah Gadang Mande Rubiah, and the reasons why the preservation of Rumah Gadang is important. In writing this article, the method used is the Systematic Literature Review (SLR) method, by first collecting study materials related to the importance of cultural preservation at Mande Rubiah's Gadang House, both in the form of books, articles, and other sources.